Rescue of the historical-cultural heritage of the Yanesha: interculturality and inclusive education of the oral traditions - Olguín Martínez, Cynthia Michel; Bracho Rivera, Rene Isaac; Ramos Perez, Rita Liss; Villacorta Guzmán, Juan Richar; Romero Carazas, Rafael; Rosillo Suárez, Nancy; Bracho Mosquera, Aaron Samuel; Mora Barajas, José Gregorio; Román Mireles, Amarelys; Rodríguez Álvarez, Aida Maygualida; Carbache Mora, César; Ormaza Esmeraldas, Elizabeth del Carmen; et al. (Multidisciplinar (Montevideo), 2024)
Interculturality based on customs, dialects, historical, linguistic and oral traditions are essential for the construction of a just, inclusive and equitable society. Hence the importance of the diverse participation of children from original families who through their own expressions exercise their learning of citizenship in schools, which is usable from an early age and also based on sharing these through their parents with the aim of settling in the child. However, there has been little progress in practical experience of this inclusion and reassessment at the pedagogical level. This article sought to open reflective spaces and deliberation about the importance of oral traditions within the rescue of the historical cultural heritage of the Yanesha under an intercultural approach and inclusive education. The research was carried out in a case study of ethnographic methods carried out throughout the academic year 2019-2020, which hovers over participatory observation, unstructured interviews and documentary analysis, taking into consideration 5 oral traditions narrated by Ayllu parents of the Yanesha people of the Hauswald Initial Educational Institution. The results indicated that it is possible to establish actions focused on oral traditions to favor the teaching of values and nurture cultural inclusion in the children of the institution. Thus, the inescapable attention to interculturality from an external level of the Initial Educational Institution Hauswald is an enriching opportunity for established educational trends that value diversity, especially for being in a country diverse in culture, language and ethnicity and because it is one of the competencies of future generations